Relaco: a product to reduce water shoot formation around pruning wounds in pome fruit trees - Csiszár, L.; Újvári, M.; Panea, T. (International Journal of Horticultural Science, 2001)
Larger cuts made during the winter pruning of pome fruit orchards a number of serious problems: the wounds serve as entrances for several branch-infecting pathogens, the numerous water shoots formed around the cut edges consume assimilates, shade the developing fruits, make the canopy dense, reduce the effectiveness of the pest management and cause extra work during next seasons pruning work. These problems can be eliminated by using proper wound protectants, like Relaco, a new Romanian wound protectant to cover larger pruning cuts of apple, pear and quince trees.The treaments by Relaco resulted in a significant decrease in both the number and total length of water shoots formed around the cut egdes.